Agricultural policy and the Common Market - Marsh, John Stanley; Ritson, Christopher (London : Chatham House; PEP, 1971)
This study examines the character and development of agricultural policy within the European Economic Community. The study starts with a brief outline of the Common Agricultural Policy (CAP). Chapter 2 states briefly the theoretical background against which agricultural policy decisions need to be set. It is followed by an examination of decisions taken by the Community in chapter 3. In chapter 4, the possibility of improving policy by extending the use of mechanisms which already exist within the Community is discussed. Chapter 5 looks at the present agricultural arrangements of the Community in relation to the United Kingdom.
Includes bibliographical references.
ne 21/06/2018
Loans
Keywords: Agriculture and state; Agricultural policy